Excellent Outcomes With Reduced Frequency of Vincristine and Dexamethasone Pulses in Standard-Risk B-Lymphoblastic Leukemia: Results From Children's Oncology Group AALL0932. Issue 13 (1st May 2021) - Angiolillo, Anne L.; Schore, Reuven J.; Kairalla, John A.; Devidas, Meenakshi; Rabin, Karen R.; Zweidler-McKay, Patrick; Borowitz, Michael J.; Wood, Brent; Carroll, Andrew J.; Heerema, Nyla A.; Relling, Mary V.; Hitzler, Johann; et al.
Abstract : Purpose: AALL0932 evaluated two randomized maintenance interventions to optimize disease-free survival (DFS) while reducing the burden of therapy in children with newly diagnosed NCI standard-risk (SR) B-acute lymphoblastic leukemia (B-ALL). Methods: AALL0932 enrolled 9, 229 patients with B-ALL; 2, 364 average-risk (AR) patients were randomly assigned (2 × 2 factorial design) at the start of maintenance therapy to vincristine/dexamethasone pulses every 4 (VCR/DEX4) or every 12 (VCR/DEX12) weeks, and a starting dose of weekly oral methotrexate of 20 mg/m 2 (MTX20) or 40 mg/m 2 (MTX40). Results: Five-year event-free survival and overall survival (OS) from enrollment (with 95% CIs), for all eligible and evaluable SR B-ALL patients (n = 9, 226), were 92.0% (91.1% and 92.8%) and 96.8% (96.2% and 97.3%), respectively. The 5-year DFS and OS from the start of maintenance for randomly assigned AR patients were 94.6% (93.3% and 95.9%) and 98.5% (97.7% and 99.2%), respectively. The 5-year DFS and OS for patients randomly assigned to receive VCR/DEX4 (n = 1, 186) versus VCR/DEX12 (n = 1, 178) were 94.1% (92.2% and 96.0%) and 98.3% (97.2% and 99.4%) v 95.1% (93.3% and 96.9%) and 98.6% (97.7% and 99.6%), respectively ( P = .86 and .69). The 5-year DFS and OS for AR patients randomly assigned to receive MTX20 versus MTX40 were 95.1% (93.3% and 96.8%) and 98.8% (97.9% and 99.7%) v 94.2% (92.2% and 96.1%) and 98.1% (97.0% and 99.2%), respectively ( P = .92 and .89). Conclusions: The 0NCI-SR AR B-ALL who received VCR/DEX12 had outstanding outcomes despite receiving one third of the vincristine/dexamethasone pulses previously used as standard of care on Children's Oncology Group (COG) trials. The higher starting dose of MTX of 40 mg/m 2 /week did not improve outcomes when compared with 20 mg/m 2 /week. The decreased frequency of vincristine/dexamethasone pulses has been incorporated into frontline COG B-ALL trials to decrease the burden of therapy for patients and their families.